Pelatihan Penguatan Komunitas Belajar Sekolah–Pesantren dalam Pengembangan Spiritualitas dan Etika Sosial di Kabupaten Sleman, Yogyakarta - Ahmad Fawzi; Siti Nurhayati; Rifqi Hidayat; Lina Rahmawati; Muhammad Iqbal; Dewi Lestari; Hafiz Pratama (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aims to strengthen school–pesantren learning communities in developing spirituality and social ethics in Sleman Regency, Yogyakarta. The program background addresses the need to integrate spiritual values into formal learning processes to foster students’ ethical character. The implementation employed a participatory approach through structured training, continuous mentoring, and the establishment of communities of practice over a six-month period. The activities involved 85 educators from 12 educational institutions, covering materials on transformative spirituality, contemporary social ethics, and values-based leadership. The results indicate a significant improvement in educators’ capacity to integrate spiritual–ethical values into learning, the development of contextual learning modules, and the strengthening of inter-institutional collaborative networks. In conclusion, the program successfully built a holistic learning ecosystem that balances cognitive, affective, and spiritual dimensions in the character development of the younger generation.